The Predominance of Female Ghost Characters in Indonesian Movies in the Period 2020-2025: Social Culture Perspective - Alvita Nurliani; Olivia Aida Sabrina; Euis Meinawati (Universitas Islam Negeri Palopo, 2026)
This article examines the portrayal of female ghost characters in 30 Indonesian horror movies released between 2020 and 2025, analyzing their prevalence through the lens of Stuart Hall's theory of representation. A qualitative approach will be employed for the purpose of examination. The study posits that female ghosts serve as potent symbolic representations of social and cultural anxieties. A tripartite framework is used, focusing on the construction of language, images, and cultural symbols with the main analytical categories: gender norms, ritual practices, mythology, and spiritual beliefs. The data reveal that female ghosts are used to symbolise women who have been violated, betrayed, or forced to transgress established socio-cultural boundaries. The continued predominance of these figures reflects the horror genre's crucial function as a cultural tool for reflecting and regulating society's most deeply rooted gender ideologies.